Environmental engagement of costumer in the tourism industry - Campos-Soria, Juan Antonio; García-Pozo, Alejandro; Fernández-Gámez, Manuel Ángel (My University, 2018)
This article contributes to a better understanding of tourists’ environmental concerns, assuming that distance from the place of residence is relevant. The analysis is conducted for EU-27 countries, combining micro-data, correspond to the Flash Eurobarometer 281 drawn from the European Commission and macro-data from different international sources. Since the environmental attitudes may vary across different cultures and societies, the individuals should be nested into countries. Therefore, it is inappropriate to analyze data using traditional regression analysis. Mixed model specifically may take into account such hierarchical data structure considering simultaneously individual and contextual variables. A general finding from the estimates indicated that significant variance exists within and among nations in the level of environmental support. This finding is congruent with the necessity of simultaneously assessing the effect of individual and country levels variables on environmental support across the European countries. Additionally, this paper demonstrates that people who are actively involved in protecting the environment at home do not maintain this type of behavior when they go on vacation, which may have negative environmental consequences on destinations, albeit involuntarily. The environmental concerns of tourists when travelling domestically were around 15% higher than those travelling abroad. Additionally, the random slope variance regarding destination choice parameter is statistically significant, which allows us to explore the underpinning behind the heterogeneous pattern across countries. Our results can be of great importance to minimize the negative environmental impacts when traveling, and represents an interesting starting point to reduce the environmentally unsustainable behaviors in the tourist field.
Keywords: Turismo; Tourist´s environmental attitudes; Multilevel analysis; Country of origin; Destination choice